Characterization of spontaneous imbibition dynamics in irregular channels by mesoscopic modeling. (30th May 2018) - Zheng, Jiangtao; Chen, Zhiqiang; Xie, Chiyu; Wang, Ziyan; Lei, Zhengdong; Ju, Yang; Wang, Moran
Highlights: Improved fluid-solid interaction force is proposed in the pseudopotential LBM. Accurate simulation of spontaneous imbibition is permitted with fewer grid nodes. Spontaneous imbibition in irregular channels is simulated and analyzed. Meniscus propagation in bifurcated channels is quantitatively studied. Abstract: Accurate knowledge of spontaneous imbibition in irregular channels is fundamentally important for a better understanding of the transport in a porous media. During the spontaneous imbibition, the wetting fluid is driven by the capillary pressure and retarded by the viscous drag, both of which are highly influenced by the channel geometry. As a result, accurate simulation of the process in complex geometries becomes important. In this study, an improved fluid-solid interaction force in the two-phase pseudopotential lattice Boltzmann method is proposed for the accuracy and stability in simulating the spontaneous imbibition behavior. After validation the simulated results against the theoretical results in a 2D straight channel, the method is employed to simulate the spontaneous imbibition in irregular channel models, which include a sine-shape channel, a wedge-shape channel and bifurcated channels. The results quantitatively revealed the influence of tortuosity, channel shape on the imbibition behavior and the competing interfaces advancing behavior in bifurcated channels.